Persen Hidup Tanaman pada Area Showing Window Revegetasi Lahan Gambut Bekas Terbakar di HLG Londerang : Plant Survival Rate at Revegetation Showing Window Area Of Burned Peatland In Hlg Londerang - Napitupulu, Richard RP (Jurnal Silva Tropika, 2022)
ABSTRACT Forest and peatland fires in Jambi leave a very large degraded peat area, one of which is in the Londerang Peat Protection Forest (HLG), which mostly leaves empty peatlands with severe damage. Rehabilitation efforts have been carried out by The Korea Indonesia Forest Center (KIFC) through planting activities covering an area of 200 ha. The purpose of the study was to determine the survival rate of rehabilitation plants in the showing window area. A total of 6 (six) measuring plots were placed in the showing window area along the main inpection road of the rehabilitation area. Each measuring plot is made 25 m x 40 m so that the area is 0.1 ha. Measurement data include the number of living plants, plant height and plant diameter. The results showed that the survival rate of rehabilitation plant in the showing window area was 100%. Rehabilitation plant growth was also very good with the average height and diameter of Dyera lowii respectively 58.91 cm and 13.44 mm, Alstonia penumatophora 70.38 cm and 12.77 mm, and Shorea balangeran 56.04 cm and 4.66 mm. Keywords: rehabilitation, peat, Dyera lowii, Alstonia penumatophora, Shorea balangeran ABSTRAK Kebakaran hutan dan lahan gambut di Jambi menyisakan gambut terdegradasi yang sangat luas, salah satunya di Hutan Lindung Gambut (HLG) Londerang, yang sebahagian besar menyisakan lahan gambut kosong dengan tingkat kerusakan parah. Telah dilakukan upaya rehabilitasi oleh Korea Indonesia Forest Center (KIFC) melalui kegiatan penanaman seluas 200 ha. Tujuan penelitian adalah untuk mengetahui seberapa besar persen hidup (survival rate) tanaman rehabilitasi pada area showing window. Sebanyak 6 (enam) petak ukur ditempatkan pada area showing window di sepanjang jalan inpeksi utama areal rehabilitasi. Setiap petak ukur dibuat berukuran 25 m x 40 m sehingga luasannya 0,1 ha. Data pengukuran meliputi jumlah tanaman yang hidup, tinggi tanaman dan diameter tanaman. Hasil penelitian menunjukkan bahwa tanaman rehabilitasi pada area showing window memiliki persen hidup 100%. Pertumbuhan tanaman rehabilitasi juga sangat baik dengan rerata tinggi dan diameter jelutung rawa 58,91 cm dan 13,44 mm, pulai rawa 70,38 cm dan 12,77 mm, serta balangeran 56,04 cm dan 4,66 mm. Kata Kunci: rehabilitasi, gambut, pulai rawa, jelutung rawa, balangeran